Activation of PI3K/p110α in the Lung Mesenchyme Affects Branching Morphogenesis and Club Cell Differentiation - Dai, Haiting; Zhu, Mingli; Li, Wenya; Si, Guohui; Xing, Yiming (Frontiers in Cell and Developmental Biology, 2022)
Epithelial-mesenchymal interaction is required for normal growth, morphogenetic patterning, and cellular differentiation in the developing lung. Various signaling pathways have been defined in establishing the patterning of this branched organ. The phosphoinositide-3-kinase (PI3K) signaling plays important roles in disease pathogenesis but remains largely uncharacterized in embryonic development. In this study, we activated a specific catalytic subunit of PI3K catalytic enzymes, Class IA p110α (p110α), in the embryonic lung mesenchyme using the Dermo1-Cre mouse. Activation of p110α promoted branching morphogenesis and blocked Club cell differentiation in both proximal and distal airways. Mechanistically, LIM homeodomain gene Islet-1 (Isl1), fibroblast growth factor 10 (Fgf10) and SRY (sex determining region Y)-box9 (Sox9) were found to be downstream targets of p110α. The significantly increased expressions of Isl1, Fgf10 and Sox9 resulted in stimulation of branching in mutant lungs. Activation of p110α-mediated signaling also increased the expression of phosphatase and tensin homolog deleted on Chromosome 10 (Pten) and hairy/enhancer of split 1 (Hes1), which in turn blocked Club cell differentiation. Thus, the signaling pathway by which PI3K/p110α regulated epithelial-mesenchymal interactions may entail Isl1-Fgf10-Sox9 and Pten-Hes1 networks, which consequently regulates branching morphogenesis and Club cell differentiation respectively.